A Variable-Force Variable-Flavor Attitude Verb in Koryak - Močnik , Maša; Abramovitz, Rafael (Proceedings of the Amsterdam Colloquium, 2019)
We enrich the typology of modal expressions with the attitude verb ivək from Koryak, which shows a wide range of flavors (doxastic, bouletic, assertive, directive) and is the first documented variable-force attitude verb. Variation in both domains goes against the universal that modal items can’t vary in both force and flavor (Nauze 2008). We use the existential-universal doxastic-assertive variation to argue against this generalization. For the bouletic flavor, we show that it is triggered by the material in the embedded clause; we propose a new technical way of composing the bouletic flavor at LF.